Long-term evolution of renal function in patients with type 2 diabetes mellitus: a registry-based retrospective cohort study. Issue 12 (30th December 2013) - Goderis, Geert; Van Pottelbergh, Gijs; Truyers, Carla; Van Casteren, Viviane; De Clercq, Etienne; Van Den Broeke, Carine; Buntinx, Frank
Abstract : Objectives: To picture the 10-year evolution of renal function in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) and to describe the risk factors for severe decline. Setting: Primary registration network with 97 general practitioners working in 55 practices sending routinely collected patient data. Participants: From the database, we selected all patients aged 40 years or older with T2DM and at least two creatinine measurements in two different years with an interval of at least 3 months. Based on the last available value of estimated glomerular filtration rate calculated by the modification of diet in renal disease (MDRD) equation, patients were divided into grades of CKD. Severe decline (decline of >4 mL/min/year) and 'certain drop' (CD, year-to-year decline >10 mL/min) were determined in patients with CKD. Determinants of severe decline and CD were investigated with logistic regression and longitudinal logistic regression analysis, respectively. Primary outcome measure: Kidney function (MDRD). Results: 4041 patients, 1980 women, were included. The mean age was 71 years, mean diabetes duration was 7.7 years; 1514 (38%) suffered from CKD, 231 (15%) presented with severe decline and 18% of the patients with CKD presented with two or more CDs. Younger age, male gender, mean glycated haemoglobin and a higher number of CDs were significantly associated with the presence of severe decline (p<0.05); statins and higher diastolic blood pressure were significantly associated with the absence of severe decline (p<0.001). ACE inhibitors, other antihypertensive drugs and antidiabetic drugs including insulin therapy were specific determinants of CD. Conclusions: CKD is highly prevalent in patients with T2DM; a minority of patients evolve into severe decline that is associated with younger age, male gender, 'CD' and manageable factors such as blood pressure, blood glucose, associated drugs prescriptions and statin therapy. Further prospective observational and experimental research is needed to clarify the nature of those associations.